Identification of the Type and Density of Water Plants in Teluk Petai Lake, Buluh Village, Siak Hulu District, Riau Province - Devi, Fransiska Rivana; Efawani, Efawani; Eddiwan, Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractTeluk Petai Lake is one of the oxbow lakes in the Buluh Nipis Village. This lake is inhibited by various types of aquatic plants and they almost cover the surface of the lake. A study aims to understand the types and density of the aquatic plants was conducted from October to November 2020. A survey method was applied.   Aquatic plant samplings were conducted 4 times, within a month period. The plants collected were then identified based on Van Steenis (1981). Results shown that there were 7 species of aquatic plants present and they are belonged to 5 classes and 7 families. They are Eichhornia crassipes, Ipomoea aquatica, Salvinia natans, Myriophyllum spicatum, Polygonum sp., Paspalum commersonii and Heminthus micranthemoides. The most common plant is Eichhornia crassipes (23-31 organisms/m2) with relative density ranged from 27.87 to 42.04 %. While the rarest was Paspalum commersonii (17.2 organisms/m2) with relative density 21.00 % and biomass (12,6-25,4 g). In general, the relative density of the aquatic plants in Teluk Petai Lake can be categorized as rare to moderate.Keyword: Oxbow Lake, Riparian Plant, Eichhornia crassipes